Evaluating Microplastic Concentrations in the Al Hoceima Marine Protected Area: Implications for Identifying Pollution Hotspots and Formulating Conservation Strategies - Bouazzati, Hasna; Damghi, Asma; El M'rini, Abdelmounim; Karim, Souhail; Maanan, Mohamed (Sustainable Marine Structures, 2025)
Global marine ecosystems are significantly endangered by microplastic pollution, leading to comprehensive investigations into its distribution and impacts  on the health of ecosystem. This research employs  the Alseamar Autonomous Underwater Vehicle (AUV) known as Glider  to investigate microplastic concentrations within the Al Hoceima Marine Protected Area (MPA). Our objective is to identify spatial patterns that reveal pollution hotspots and furnish data for targeted conservation efforts and pollution prevention. We aim to identify regions with elevated microplastic concentrations by meticulously analyzing microplastic level graphs, with a specific focus on temporal variations. The results reveal notable patterns, such as increased densities around fishing harbors and near urban centers , potentially linked to anthropogenic activities. Additionally, we observe variations in pollution levels throughout different glider operation cycles, underscoring the importance of understanding the spatio-temporal dynamics of microplastic distribution. Al Hoceima Marine protected areas exhibiting lower microplastic concentrations illustrate the efficacy of such zones in alleviating pollution impacts, thereby underscoring the significance of conservation efforts in safeguarding marine biodiversity and ecosystem resilience. Ultimately, our research enhances our comprehension of the pressures exerted by humans on marine environments and underscores the necessity of proactive conservation measures to shield marine ecosystems from the threats posed by microplastic pollution. ER